Abscisic acid promotes jasmonic acid biosynthesis via a 'SAPK10‐bZIP72‐AOC' pathway to synergistically inhibit seed germination in rice (Oryza sativa). Issue 4 (28th July 2020) - Wang, Yifeng; Hou, Yuxuan; Qiu, Jiehua; Wang, Huimei; Wang, Shuang; Tang, Liqun; Tong, Xiaohong; Zhang, Jian
Summary: Abscisic acid (ABA) and jasmonic acid (JA) both inhibit seed germination, but their interactions during this process remain elusive. Here, we report the identification of a 'SAPK10‐bZIP72‐ AOC ' pathway, through which ABA promotes JA biosynthesis to synergistically inhibit rice seed germination. Using biochemical interaction and phosphorylation assays, we show that SAPK10 exhibits autophosphorylation activity on the 177 th serine, which enables it to phosphorylate bZIP72 majorly on 71 st serine. The SAPK10‐dependent phosphorylation enhances bZIP72 protein stability as well as the DNA‐binding ability to the G‐box cis ‐element of AOC promoter, thereby elevating the AOC transcription and the endogenous concentration of JA. Blocking of JA biosynthesis significantly alleviated the ABA sensitivity on seed germination, suggesting that ABA‐imposed inhibition partially relied on the elevated concentration of JA. Our findings shed a novel insight into the molecular networks of ABA–JA synergistic interaction during rice seed germination.